WEB-BASED TEACHER AND STUDENT DATA INFORMATION SYSTEM OF SDN 19 SUMBER MARGA TELANG - Ambo Asse; Dedi Haryanto (International Journal Cister, 2022)
With reference to the background of the problem above, the formulation of the problem to be discussed is formulated, namely "How is the student data management information system at SDN 19 Sumber marga telang?". The method used in this research is a quantitative research method with a descriptive approach. Quantitative research method is one type of research whose specifications are systematic, well-planned and clearly structured from the beginning to the making of the research design. Based on the results of the Blackbox test, it can be concluded that the purpose of this research has been achieved and designed an information system for managing data for SDN Sumber marga telang students computerized using the PHP programming language and using the Mysql database which can make it easier for staff to manage data and obtain the required information. quality and can assist in the decision-making process